Divergence within the Taxon ‘Candidatus Phytoplasma asteris’ Confirmed by Comparative Genome Analysis of Carrot Strains - Rafael Toth; Anna-Marie Ilic; Bruno Huettel; Bojan Duduk; Michael Kube (Microorganisms, 2024)
Phytoplasmas are linked to diseases in hundreds of economically important crops, including carrots. In carrots, phytoplasmosis is associated with leaf chlorosis and necrosis, coupled with inhibited root system development, ultimately leading to significant economic losses. During a field study conducted in Baden-Württemberg (Germany), two strains of the provisional taxon ‘Candidatus Phytoplasma asteris’ were identified within a carrot plot. For further analysis, strains M8 and M33 underwent shotgun sequencing, utilising single-molecule-real-time (SMRT) long-read sequencing and sequencing-by-synthesis (SBS) paired-end short-read sequencing techniques. Hybrid assemblies resulted in complete de novo assemblies of two genomes harboring circular chromosomes and two plasmids. Analyses, including average nucleotide identity and sequence comparisons of established marker genes, confirmed the phylogenetic divergence of ‘Ca. P. asteris’ and a different assignment of strains to the 16S rRNA subgroup I-A for M33 and I-B for M8. These groups exhibited unique features, encompassing virulence factors and genes, associated with the mobilome. In contrast, pan-genome analysis revealed a highly conserved gene set related to metabolism across these strains. This analysis of the Aster Yellows (AY) group reaffirms the perception of phytoplasmas as bacteria that have undergone extensive genome reduction during their co-evolution with the host and an increase of genome size by mobilome.